Immune checkpoint inhibitors for treatment of periorbital squamous cell carcinoma. Issue 3 (8th October 2021) - Goldfarb, Jeremy Allan; Ferrarotto, Renata; Gross, Neil; Goepfert, Ryan; Debnam, James Matthew; Gunn, Brandon; Nagarajan, Priyadharsini; Esmaeli, Bita
Abstract : Purpose: To report on the outcomes of immunotherapy in patients with locally advanced periorbital squamous cell carcinoma. Methods: We performed a retrospective chart review of seven consecutive patients with locally advanced periorbital cutaneous squamous cell carcinoma treated with anti-PD-1 immunotherapy. Treatments and therapeutic outcomes were reviewed. Results: Of the seven patients, six were treated with cemiplimab, and one was treated with pembrolizumab. Five patients were treated with immunotherapy as neoadjuvant therapy before planned surgical resection; two patients received immunotherapy for treatment of advanced recurrent lesions deemed unresectable following multiple previous excisions and radiation therapy. In all seven patients, measurable clinical and/or radiologic response was observed. Conclusions: Our findings support the emerging role of anti-PD-1 immunotherapy in the management of locally advanced periorbital cutaneous squamous cell carcinoma.